ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK - Andika, Bagus; L. Tobing, Vargo Christian (SCIENTIA JOURNAL, 2023)
This study aims to to determine the factors that influence the interest of accounting studentsin choosing a career as a public accountant. The data analysis method used in this studyconsisted of descriptive statistical tests, data quality tests, consisting of validity and reliabilitytests, classical assumption tests, multiple linear regression tests, coefficient of determinationtests, and hypothesis testing consisting of t tests and f tests. The results of testing thehypothesis in this study indicate that partially financial rewards, job market considerations,and professional training have a positive and significant effect on the interest of accountingstudents in choosing to become public accountants, and simultaneously financial rewards,job market considerations, and professional training have a positive effect and significant tothe interest of accounting students in choosing a career as a public accountant. The testresults for the coefficient of determination in this study were 0.551, so the independentvariables in this study had an influence on the dependent variable of 55.1%, the remaining44.9% were influenced by other variables outside this study